2017
DOI: 10.12820/rbafs.v.22n3p213-216
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Physical Activity Promotion: Where is Brazil?

Abstract: In 2011, Hallal and Florindo argued that the evaluation of interventions to increase physical activity would be an important field within physical activity epidemiology in the following years 1 . Their argument turned out to be true. In the global context, we had a massive increase in studies on interventions in the last ten years. While writing this editorial, we searched PubMed and Web of Science, looking for systematic reviews with the words "intervention" and "physical activity" in their titles. We found 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
0
0
1
Order By: Relevance
“…Our study suggests that strong collaborations between researchers and front-line public health workers can enhance the efficacy of an intervention. This finding is consistent with the conclusions of a prior study which found that joint action between researchers, managers, and professionals can be an efficient strategy in the formulation, application, evaluation, and control of public health interventions (Florindo & Guerra, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Our study suggests that strong collaborations between researchers and front-line public health workers can enhance the efficacy of an intervention. This finding is consistent with the conclusions of a prior study which found that joint action between researchers, managers, and professionals can be an efficient strategy in the formulation, application, evaluation, and control of public health interventions (Florindo & Guerra, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Diante desse cenário, ações que promovam a prática de AF têm sido implementadas em diversos setores, como na atenção primária à saúde, no ambiente escolar, na comunidade, nos ambientes de trabalho, transporte e planejamento urbano [5][6][7][8] . Entre as estratégias para a promoção de AF, o aconselhamento tem apresentado efeitos positivos em tornar os sujeitos mais ativos, seja prescrito em grupos ou individualmente 9 .…”
Section: Introductionunclassified